Chemistry of materials celebrates the 80th birthday of one of the premier "chemists of materials" - Prasad, Bhagavatula L. V; Buriak, Jillian M. (Chemistry of Materials, 2014)

Digestive ripening of Au nanoparticles by multidentate ligands - Sahu, Puspanjali; Shimpi, Jayesh; Lee, Han Ju; Lee, T. Randall; Prasad, Bhagavatula L. V (Langmuir, 2017)
The efficiency of multidentate ligands as digestive ripening agents for the preparation of monodisperse Au nanoparticles was investigated. This systematic investigation was performed using ligands possessing one, two, or three thiol moieties as ligands/digestive ripening agents. Our results clearly establish that among the different ligands, those that are monodentate and the use of temperatures in the range of 60 °C and 120 °C offer the best conditions for digestive ripening. In addition, when digestive ripening was carried out at lower temperatures (e.g., 60 °C), the nanoparticle size increased as the number of thiol groups per ligand increased. However, in the case of ligands possessing two and three thiol moieties when they are heated with polydispersed particles at higher temperatures (120 °C or 180 °C), the etching process dominates, which affects the quality of the nanoparticles in terms of their monodispersity. We conclude that the temperature-dependent strength of the interaction between the ligand headgroup and the nanoparticle surface plays a vital role in controlling the final particle sizes.